Nemesis - Nesbo, Jo, 1960- (Vintage Books, 2009)
How do you catch a killer when you're the number one suspect? A man is caught on CCTV, shooting dead a cashier at a bank. Detective Harry Hole begins his investigation, but after dinner with an old flame wakes up with no memory of the past 12 hours. Then the girl is found dead in mysterious circumstances and he begins to receive threatening emails: is someone trying to frame him for her death? As Harry fights to clear his name, the bank robberies continue with unparalleled savagery... (From the publisher)